Radiation Retinopathy/Maculopathy: A Case Report - Farrukh Jameel, Hussain Ahmad Khaqan, Usman Imtiaz (Pakistan Journal of Ophthalmology, 2016)
A 29-year-old male presented to OPD with complaint of decreased vision in Left eye. About 6months back he was diagnosed with Myxofibrosarcoma of the left zygomatic bone. Patient underwent radiation therapy for the tumor. 3 months after the last session of radiotherapy, patient experienced decreased vision in left eye. VA was 6/6 OD and 6/36 OS. Anterior segment examination revealed madarosis, trichiasis and conjunctival congestion of left eye. Fundus examination of the left eye showed cotton wool spots, intraretinal hemorrhages and macular edema. Patient was given intravitreal injection Bevacizumab (Avastin) 1.25 mg/ 0.05 ml in the left eye. After 4 weeks of the injection VA was improved to 6/9 in left eye. Patient was asked to have a monthly follow-up. On the 5thfollow-up vision was again reduced to 6/18 OS. OCT revealed increased macular thickness. Patient was again advised intravitreal injection Bevacizumab. 3 injections were given monthly. Vision improved to 6/6 OS and patient is still on follow-up for 18 months. Anti-VEGF Bevacizumab is effective in the treatment of radiation associated macular edema. Key Words: Radiation retinopathy Bevacizumab, intraretinal hemorrhages.